2005
DOI: 10.1111/j.1742-1241.2005.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological features of liver and its relation to serum transaminase levels in 91 cases of anti-HBe-positive chronic hepatitis B

Abstract: For assessing the histopathological features and its relation to alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels in anti-HBe-positive chronic hepatitis B in Babol, north of Iran, liver biopsy samples of 91 anti-HBe-positive chronic hepatitis B virus (HBV) infection with raised ALT were scored according to histological hepatitis activity index (HAI) from March 2000 to July 2003. Seventy-seven males and 14 females with a mean age of 32.24 (+/-11.92) years were studied. Mean ALT and AST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…In liver diseases such as in viral hepatitis, the liver cells spill the enzymes into the blood, raising the enzyme levels in the blood and signaling that the liver was damaged (8). In a study which was investigated relationship between histopathological features of liver and serum transaminase levels, AST was found a better laboratory screening test for finding the severity of liver injury than ALT in HBeAgnegative CHB patients (9). Similarly, our results showed that AST levels are more useful in showing liver damage than ALT.…”
Section: Discussionsupporting
confidence: 61%
“…In liver diseases such as in viral hepatitis, the liver cells spill the enzymes into the blood, raising the enzyme levels in the blood and signaling that the liver was damaged (8). In a study which was investigated relationship between histopathological features of liver and serum transaminase levels, AST was found a better laboratory screening test for finding the severity of liver injury than ALT in HBeAgnegative CHB patients (9). Similarly, our results showed that AST levels are more useful in showing liver damage than ALT.…”
Section: Discussionsupporting
confidence: 61%
“…This association between viral load and high transaminase values has already been observed in previous studies; A study has already reported the relationship between HBV-DNA values and high ALT levels in 110 chronic HBeAg-negative individuals, however the same was not observed for AST [ 22 ]. An evaluation of 91 patients observed a greater sensitivity of AST for the detection of liver damage, which may suggest that AST dosage would be more indicated as a screening test for evaluation in these cases [ 23 ]. In a study by researchers in China with 11,738 treatment-naïve adult patients, fifty-five percent of patients with HBV-DNA ≥20,000 IU/mL had abnormal ALT and/or AST values, which was significantly higher than in patients with HBV-DNA levels below 20,000 IU/mL [ 22 ].…”
Section: Discussionmentioning
confidence: 99%